An Updated Literature Review of Distance Correlation and Its Applications to Time Series. (27th September 2018) - Edelmann, Dominic; Fokianos, Konstantinos; Pitsillou, Maria
Summary: The concept of distance covariance/correlation was introduced recently to characterise dependence among vectors of random variables. We review some statistical aspects of distance covariance/correlation function, and we demonstrate its applicability to time series analysis. We will see that the auto‐distance covariance/correlation function is able to identify non‐linear relationships and can be employed for testing the i.i.d. hypothesis. Comparisons with other measures of dependence are included.